2008
DOI: 10.1016/j.canlet.2007.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 8 load and progression of AIDS-related Kaposi sarcoma lesions

Abstract: Introduction-Human herpesvirus 8 (HHV8) is necessary for Kaposi sarcoma (KS) to develop, but whether peripheral blood viral load is a marker of KS burden (total number of KS lesions), KS progression (the rate of eruption of new KS lesions), or both is unclear. We investigated these relationships in persons with AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 26 publications
3
29
0
1
Order By: Relevance
“…Another study showed that measurement of the HHV8 load [33]. A recent study performed in AIDS-related KS from Uganda demonstrated that the HHV8 load in peripheral blood was positively and significantly associated with the rate of KS progression but not with the KS burden [34]. Finally, a clinical scoring system to predict survival in HIV-associated KS, which includes the CD4 count, age, association with another AIDS-associated illness, has been established previously in cases with KS as the AIDS-defining illness [35].…”
Section: Discussionmentioning
confidence: 95%
“…Another study showed that measurement of the HHV8 load [33]. A recent study performed in AIDS-related KS from Uganda demonstrated that the HHV8 load in peripheral blood was positively and significantly associated with the rate of KS progression but not with the KS burden [34]. Finally, a clinical scoring system to predict survival in HIV-associated KS, which includes the CD4 count, age, association with another AIDS-associated illness, has been established previously in cases with KS as the AIDS-defining illness [35].…”
Section: Discussionmentioning
confidence: 95%
“…These covariates were anchored in the model based on clinical knowledge and previous literature that suggested they may be associated with the variables of interest [10-12]. Data were stored in Microsoft Excel 2010 and analyzed using Stata/SE v.11.0 (College Station, Texas).…”
Section: Methodsmentioning
confidence: 99%
“…Cross sectional studies of HHV-8 plasma viremia in patients with epidemic KS have shown an association with KS stage [16] and KS progression, but not KS burden [17]. The role of HHV-8 replication in non-epidemic forms of KS is less clear.…”
Section: Introductionmentioning
confidence: 99%